Use of ‘Sampling’ Technique in Urdu Research: An Analysis - Dr. Muhammad Hamid; Dr. Salma Aslam (دریافت)
Sampling is an important technique used in the modern research in social sciences. The technique covers a large kinds of research with ease. Its main kinds are probability and non-probability sampling, and both are used in research to draw reliable and trustworthy results. Sampling is used in literary and historical research too. The sub-techniques of non-probability sampling like purposive sampling, convenience sampling, judgement sampling have been used in Urdu research, but no researcher uses the term ‘sampling’ in their research report. Several researchers clearly describe their research methodology in dissertations, still they do not mention sampling, despite the use of it in the research. A good hand on the use of sampling is need of the modern research, so it should be included in the curriculum of research methodology in universities. This article is based on the study of 50 theses, which secured through systematic random sampling. The findings have been drawn from the samples and applied on the whole types. Conclusion has been presented based on findings.